Upaya Guru dalam Meningkatkan Keterampilan Berbicara Siswa Kelas 3 SD Hikmah 1 Yapis Jayapura - Samuel Mamonto; M. Fitrah Pratama (Journal on Education, 2024)
This research aims to improve the speaking ability of students in third grade at SD Hikmah I Yapis Jayapura as well as the teacher's efforts, namely 1). The teacher uses storytelling strategies, 2). The teacher uses group discussion strategies, 3). Children repeat the story that the teacher has told, 4). The teacher provides motivational rewards in the form of "Star Signs". The implications of the teacher's efforts to improve the speaking skills of the students at SD Hikmah I Yapis Jayapura include for students (a) students can continue to learn speaking skills through anything (b) students can develop speaking skills by making videos telling the results of observations in the Indonesian language learning subject according to the theme. For teachers (a) Teachers are helped in the KBM (Teaching and Learning Activities) process, (b) make learning easier, and can continue other work.